Matrix metalloproteinase-9 and matrix metalloproteinase-2 gene polymorphisms in multiple sclerosis - Benešová, Yvonne; Vašků, Anna; Štourač, Pavel; Hladíková, Magdaléna; Beránek, Michal; Kadaňka, Zdeněk; Novotná, Hana; Bednařík, Josef (Journal of neuroimmunology, 2008)
We investigated the association of matrix metalloproteinase-9 (-1562C/T, +279R/Q) and matrix metalloproteinase-2 (-1575G/A, -1306C/T) gene polymorphisms with multiple sclerosis (MS) susceptibility, gender differences and disability in 244 patients and 132 healthy subjects. A significant decrease of the -1562T allele carriers in MS patients compared to controls (Pa=0.01, Pacorr=0.05) in -1562C/T MMP-9 gene polymorphism was found, (odds ratio (OR) -0.58, 95% confidence interval (CI):0.38-0.89). Significant differences were also demonstrated between female patients and healthy females (Pa=0.01, Pacorr=0.05), (OR-0.53, 95% CI:0.32-0.86). Other polymorphisms were not associated either with MS susceptibility or with phenotype of the disease. No association with disability was found.
Keywords: dospělí; odds ratio; matrixová metaloproteinasa 2; Female; Genotype; Adult; ženské pohlaví; Gene Frequency; lidé; Multiple Sclerosis; genotyp; roztroušená skleróza; genetická predispozice k nemoci; studie případů a kontrol; Matrix Metalloproteinase 9; Genetic Predisposition to Disease; interval spolehlivosti; frekvence genu; Confidence Intervals; Sex Factors; Male; matrixová metaloproteinasa 9; Case-Control Studies; sexuální faktory; polymorfismus genetický; lidé středního věku; mužské pohlaví; Matrix Metalloproteinase 2; Polymorphism, Genetic; Middle Aged; Odds Ratio; Humans